Born a Chief The Nineteenth Century Hopi Boyhood of Edmund Nequatewa, as told to Alfred F. Whiting - Nequatewa, Edmund (University of Arizona Press, 1993)
"Extraordinary memoir. . . . His story will break your heart."-El Palacio "This story was fascinating. . . . One worth the telling and one which will stay with the reader."-American Desert Magazine "Recommended."-Choice